Morphological and phylogenetic evidence for recognition of two new species of Hyphoderma (Basidiomycota) from southern China, with a key to all Chinese Hyphoderma - Qian-Xin Guan; Yi-Fei Li; Chang-Lin Zhao (MycoKeys, 2021)
Wood-inhabiting fungi play crucial roles as decomposers in forest ecosystems and, in this study, two new wood-inhabiting corticioid fungi, Hyphoderma puerense and H. tenuissimum spp. nov., are proposed, based on a combination of morphological features and molecular evidence. Hyphoderma puerense is characterised by effused basidiomata with smooth to floccose hymenial surface, a monomitic hyphal system with clamped generative hyphae and ellipsoid basidiospores. Hyphoderma tenuissimum is characterised by resupinate basidiomata with tuberculate to minutely-grandinioid hymenial surface, septate cystidia and cylindrical to allantoid basidiospores. Sequences of ITS and nLSU rRNA markers of the studied samples were generated and phylogenetic analyses were performed with Maximum Likelihood, maximum parsimony and Bayesian Inference methods. These analyses showed that the two new species clustered into Hyphoderma, in which H. puerense grouped with H. moniliforme and H. tenuissimum formed a singleton lineage. In addition, an identification key to Chinese Hyphoderma is provided.